2022
DOI: 10.1038/s41467-022-34345-y
|View full text |Cite
|
Sign up to set email alerts
|

The 3D enhancer network of the developing T cell genome is shaped by SATB1

Abstract: Mechanisms of tissue-specific gene expression regulation via 3D genome organization are poorly understood. Here we uncover the regulatory chromatin network of developing T cells and identify SATB1, a tissue-specific genome organizer, enriched at the anchors of promoter-enhancer loops. We have generated a T-cell specific Satb1 conditional knockout mouse which allows us to infer the molecular mechanisms responsible for the deregulation of its immune system. H3K27ac HiChIP and Hi-C experiments indicate that SATB1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 142 publications
2
19
0
Order By: Relevance
“…The above finding raised the possibility that Satb1 -a functions as an enhancer to control Satb1 gene expression in cis . To investigate this possibility, we used a publicly available three-enzyme Hi-C (3e Hi-C) dataset from murine embryonic stem cells, thymocytes, and CD4 T H 2 cells ( 22 , 23 ), to identify genome wide interactions between Satb1 -exon1 (which contain promoters) and Satb1 - a region. Interestingly, we found that Satb1 -exon1 and Satb1-a are closely located within a topologically associated domain, in both thymocytes and CD4 T H 2 cells ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…The above finding raised the possibility that Satb1 -a functions as an enhancer to control Satb1 gene expression in cis . To investigate this possibility, we used a publicly available three-enzyme Hi-C (3e Hi-C) dataset from murine embryonic stem cells, thymocytes, and CD4 T H 2 cells ( 22 , 23 ), to identify genome wide interactions between Satb1 -exon1 (which contain promoters) and Satb1 - a region. Interestingly, we found that Satb1 -exon1 and Satb1-a are closely located within a topologically associated domain, in both thymocytes and CD4 T H 2 cells ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Our group and others have recently identified the important role of the transcription factor and genome organizer SATB1 in DP thymocytes (Feng et al, 2022;Zelenka et al, 2022), where it is predominantly expressed (Zelenka and Spilianakis, 2020). SATB1 was primarily identified as a matrix associating region (MAR) binding protein (Dickinson et al, 1992;Alvarez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…FIGURE 6 (Continued)Both long and short Satb1 isoforms were produced from multiple promoters. The long SATB1 isoform binding sites were retrieved from GSE173446(Zelenka et al, 2022). (F) Human TCGA breast cancer (BRCA) patient-specific ATAC-seq peaks(Corces et al, 2018) span the extra exon (EE; labeled in green) of the long SATB1 isoform.…”
mentioning
confidence: 99%
“…SATB1 supports RAG expression and is up-regulated in DP thymocytes (8), but the breadth of its binding and its effects on the DP thymocyte transcriptional program make it difficult to discriminate direct from indirect effects on gene expression copyright © 2024 the authors, some rights reserved; exclusive licensee american association for the advancement of Science. No claim to original u.S. government Works (12,13). Thus, neither the mechanism nor the physiological importance of DP-specific elevation of RAG expression is currently understood.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of up-regulation is also poorly understood because most transcription factors critical for thymocyte expression of RAGs—including E2A, Gata3, Runx1, and Ikaros—occupy the ASE as early as the DN stage ( 9 ), and they do not have expression patterns that might explain up-regulated expression in DP thymocytes. SATB1 supports RAG expression and is up-regulated in DP thymocytes ( 8 ), but the breadth of its binding and its effects on the DP thymocyte transcriptional program make it difficult to discriminate direct from indirect effects on gene expression ( 12 , 13 ). Thus, neither the mechanism nor the physiological importance of DP-specific elevation of RAG expression is currently understood.…”
Section: Introductionmentioning
confidence: 99%